Shadow Economy impacts on Start-up vitality in selected European countries - Buszko , Andrzej (Journal of Management and Financial Sciences, 2025)
The study aims to find the relation between shadow economy and start-ups performance in selected European countries. MIMIC approach was employed to indicate the level of shadow economy. The Pearson correlation index was used to show the dependence between shadow economy and number of start-ups. It was proved that shadow economy negatively influence on start-ups activity. Additionally, the numerous start-ups in analysed countries proved to be supportive issue in unicorn creation.